AB1340-HPR PATIENTS' OUT-OF-POCKET EXPENSES ANALYSIS IN PATIENTS WITH RHEUMATOID ARTHRITIS ENROLLED IN A EDUCATIONAL PROGRAM. (2nd June 2020) - Buitrago-Garcia, D.; Rodriguez, F.; Sánchez, G.; Santos-Moreno, P.
Abstract : Background: The increasing health and economic burdens of deaths and disabilities from non-communicable diseases (NCDs) are emerging as major concerns worldwide, particularly for low- and middle-income countries (LMICs)(1). Rheumatoid arthritis (RA) NCD is considered as one of the most common causes of disability. RA affects from 0.5% to 1% of the worldwide population. Little is known about the out-of-pocket (OOP) expenditures for prescription of pharmacological treatment for patients with RA, including drugs, diagnostic tests, mobility aids among others. Objectives: To describe the out of pocket costs in patients with rheumatoid arthritis Methods: We performed a cross-sectional study among patients who are participating in an educational program in a specialized center for RA. We collected sociodemographic variables; in addition, we collected data related to the expenditures in drugs, diagnostic tests and mobility aids that were not covered by the health system. Descriptive epidemiology was done, we calculated means, and standard deviations for continuous variables and categorical variables were presented as rates. The costs are presented in the US dollars with the average exchange rate for 2019 Results: We included 181 patients, 92% were female. Mean age was 59 years ±9.5. Regarding occupation, 24% were employees, 40% were economically inactive, and 36% were pensioners. Most of patients 45% had a low income, 43 % middle income and only 12% high income according to the Colombian socioeconomic classification. Most of out of pocket expenses (47%) were associated to the acquisition of medical devices such as reading glasses or orthopedic braces. Secondly, the OOP expenses were related to medications (38%) such as antibiotics prednisone or pain control medications. Finally, 25% of patients reported that they had pay for their diagnostic tests such as x rays or laboratory tests. When assessed the costs patients expended between 30-100 USD purchasing aid devices, medications or laboratory tests. Conclusion: In the Colombian context OPP are relevant and represent an important expenditure for patients with RA especially for those who have low or middle income. Due to the above, it is important to find alternatives in order to help vulnerable segments of the population. Additionally, OPP needed to be taken into account due to its association with treatment adherence(2). References: Datta BK, Husain MJ, Fatehin S. The crowding out effect of out-of-pocket medication expenses of two major non-communicable diseases in Pakistan. International health. 2020;12(1):50-9. Acknowledgments: This project has been funded by a collaboration between the Ministry of Science, Technology and Innovation COLCIENCIAS (contract 746-2018), the Fundación Universitaria de Ciencias de la Salud and Biomab - Center for Rheumatoid Arthritis Disclosure of Interests: Diana Buitrago-Garcia: None declared, Fernando Rodriguez: None declared, GUILLERMO SÁNCHEZ: None declared, Pedro Santos-Moreno Grant/research support from: I have received research grants from Abbvie, Biopas-UCB, Janssen, Novartis, Pfizer., Speakers bureau: I have been a speaker for Abbvie, Biopas-UCB, Janssen, Lilly, Novartis, Pfizer, Roche, Sanofi.